2014
DOI: 10.1371/journal.pone.0100916
|View full text |Cite
|
Sign up to set email alerts
|

Age and Microenvironment Outweigh Genetic Influence on the Zucker Rat Microbiome

Abstract: Animal models are invaluable tools which allow us to investigate the microbiome-host dialogue. However, experimental design introduces biases in the data that we collect, also potentially leading to biased conclusions. With obesity at pandemic levels animal models of this disease have been developed; we investigated the role of experimental design on one such rodent model. We used 454 pyrosequencing to profile the faecal bacteria of obese (n = 6) and lean (homozygous n = 6; heterozygous n = 6) Zucker rats over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 57 publications
7
35
1
Order By: Relevance
“…If samples originate in animal models, particularly those involving co-housed rodents, the roles of animal age and housing environment 22,23 , and the sex of the person handling the animals 24 , may have on microbial community profiles should be taken into account. It is usually possible to mitigate against potential confounders in the study design by housing animals individually to prevent the spread of microbes between cage mates (although this may introduce behavioural changes, potentially resulting in different biases), mixing animals derived from different experimental cohorts together within the same cage, or repeating experiments with mouse lines obtained from different vendors or with different genetic backgrounds 25 .…”
Section: Shotgun Metagenomics Study Designmentioning
confidence: 99%
“…If samples originate in animal models, particularly those involving co-housed rodents, the roles of animal age and housing environment 22,23 , and the sex of the person handling the animals 24 , may have on microbial community profiles should be taken into account. It is usually possible to mitigate against potential confounders in the study design by housing animals individually to prevent the spread of microbes between cage mates (although this may introduce behavioural changes, potentially resulting in different biases), mixing animals derived from different experimental cohorts together within the same cage, or repeating experiments with mouse lines obtained from different vendors or with different genetic backgrounds 25 .…”
Section: Shotgun Metagenomics Study Designmentioning
confidence: 99%
“…Ontogenetic and temporal changes in microbial beta diversity have been detected in other aquaculture fish species as well, such as rainbow trout [33], Atlantic cod [32], and coho salmon [31]. Similar microbiota shifts are commonly detected in other organisms too, including zebrafish [13, 30], humans [5356], rodents [57, 58], and terrestrial mono-gastric livestock, such as pigs and chickens [5960]. A common theme among such research is that the newly colonized gut microbiomes of adolescent or early life stage hosts tend to exhibit higher interindividual variability and greater sensitivity to alterations, as compared to the more mature microbiomes of older hosts.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies showed that mice co-housed together exhibit similar gut microbial communities. 38,39 Thus, pooled fecal pellets from each cage were collected in 24-h metabolic cages and analyzed at three points: week 1 (baseline), week 5 (intermediate phase), and week 9 (final phase) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…As mice are coprophagic it may contribute to the development of a common microbiome in cage mates. 39 In order to minimize the potential for this confounder, we collected and analyzed pooled feces samples. Thus, compositional change in the microbial community is more likely due to dietary treatment.…”
Section: Discussionmentioning
confidence: 99%